The Development of the Bengamides as New Antibiotics against Drug-Resistant Bacteria - Porras Alcalá, Cristina; Moya-Utrera, Federico; García-Castro, Miguel; Sánchez-Ruiz, Antonio; López-Romero, Juan Manuel; Pino-González, María Soledad; Díaz-Morilla, Amelia; Kitamura, Seiya; W. Wolan, Dennis; Prados, Jose; Melguizo, Consolación; Cheng-Sánchez, Iván; et al. (IOAP-MPDI, 2022)
The bengamides comprise an interesting family of natural products isolated from sponges belonging to the prolific Jaspidae family. Their outstanding antitumor properties, coupled with their unique mechanism of action and unprecedented molecular structures, have prompted an intense research activity directed towards their total syntheses, analogue design, and biological evaluations for their development as new anticancer agents. Together with these biological studies in cancer research, in recent years, the bengamides have been identified as potential antibiotics by their impressive biological activities against various drug-resistant bacteria such as Mycobacterium tuberculosis and Staphylococcus aureus. This review reports on the new advances in the chemistry and biology of the bengamides during the last years, paying special attention to their development as promising new antibiotics. Thus, the evolution of the bengamides from their initial exploration as antitumor agents up to their current status as antibiotics is described in detail, highlighting the manifold value of these marine natural products as valid hits in medicinal chemistry.
Keywords: Antibióticos; Bengamides; Antibiotics; Drug-resistant bacteria; Antitumor agents; SAR